Fabrication and implementation of extensively dense bipolar membrane using FeCl3 as a junction catalyst - Celik, Aytekin; Hasar, Halil (Springer, 2022)
A bipolar membrane (BPM) typically consists of three layers: an acid cation-exchange layer (CEL), a base anion-exchange layer (AEL), and a junction interfacial layer with a catalyst expediting water dissociation. In this study, FeCl3 as a junction catalyst in the fabrication and applications of bipolar membranes was evaluated in detail in terms of physical, electrical characteristics and acid production performance. Results showed that using FeCl3 as catalyst in junction layer improved morphological and physical properties of BPMs. Also, FeCl3-based BPM exhibited the lowest resistance of 1.02 omega.cm(-2), the highest water uptake capacities of 25%, a maximum current efficiency of 18.8% and the highest tensile strength with 1001.4 MPa. On the other hand, while increasing of FeCl3 dosage in BPM enhanced acid recovery in the BMED system, it caused low electrical resistance.
Keywords: Bipolar membrane; Interfacial layer; Junction catalyst